2020
DOI: 10.1021/acsomega.0c03910
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid of Preeclamptic and Normotensive Pregnant Women Compared to Nonpregnant Women Analyzed with Mass Spectrometry

Abstract: Preeclampsia is a pregnancy-specific multiorgan disorder in which impaired placental functioning and excessive oxidative stress play an important role. We previously showed distinct differences between cerebrospinal fluid proteins in patients with preeclampsia and normotensive pregnant women. An additional group of nonpregnant women was included to study the presence of pregnancy-related proteins in normotensive and preeclamptic pregnancies and whether pregnancy-related proteins were associated with preeclamps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Ciampa et al demonstrated that differentially expressed proteins in the CSF of PE mothers converge to four signaling molecules, including TGF-β, vascular endothelial growth factor A, angiotensinogen, and IL-6, suggesting that neurological maternal complications of PE, such as eclampsia and posterior reversible encephalopathy syndrome, are associated with vascular remodeling, inflammation, neuronal growth, signaling, and electrophysiology ( 33 ). Güzel et al also demonstrated that some differentially expressed proteins were calcium-binding proteins, suggesting a close association between PE and calcium-binding proteins ( 34 ). As with these two studies on maternal CSF, investigation of CSF protein profiling in the offspring of the L-NAME-induced PE model may facilitate the elucidation of the mechanisms underlying subsequent neurological disorders ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ciampa et al demonstrated that differentially expressed proteins in the CSF of PE mothers converge to four signaling molecules, including TGF-β, vascular endothelial growth factor A, angiotensinogen, and IL-6, suggesting that neurological maternal complications of PE, such as eclampsia and posterior reversible encephalopathy syndrome, are associated with vascular remodeling, inflammation, neuronal growth, signaling, and electrophysiology ( 33 ). Güzel et al also demonstrated that some differentially expressed proteins were calcium-binding proteins, suggesting a close association between PE and calcium-binding proteins ( 34 ). As with these two studies on maternal CSF, investigation of CSF protein profiling in the offspring of the L-NAME-induced PE model may facilitate the elucidation of the mechanisms underlying subsequent neurological disorders ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…ESI-LC-MS/MS: The samples (eluted in 3.5, 7, and 7.5 mL) after lipid extraction in the water phase were enzymatically digested with trypsin and subsequently measured with a nano-LC-Orbitrap MS/MS mass spectrometry system (Ultimate 3000 HPLC, Thermo Fisher Scientific Germering, Germany; Orbitrap Lumos, Thermo Fisher Scientific, San Jose, CA, USA). [61] The results were valued based on the bovine dataset. Specifically, 3 μL digest was loaded onto a C18 trap column (C18 PepMap, 300 μm inner diameter (ID) Â 5 mm, 5 μm particle size, 100 Å pore size; Thermo Fisher Scientific, The Netherlands) and desalted for 10 min using a flow rate of 20 μL min À1 0.1% TFA.…”
Section: Methodsmentioning
confidence: 99%
“…Based on this survey scan, the most intense ions were consecutively isolated (AGC target set to 10 4 ions) and fragmented by collision-activated dissociation (CAD) applying 35% normalized collision energy in the linear ion trap until a duty cycle time of 3 s was reached (top speed mode). After precursors were selected for MS/MS, they were excluded for further MS/MS spectra for 60 s. Data analysis was performed as described in the study of Güzel et al [61] Statistical Analysis: GraphPad Prism version 9 was used to perform statistical analysis. All the statistical data are depicted as mean AE standard error of the mean (S.E.M.)…”
Section: Methodsmentioning
confidence: 99%
“…CDH18 has an important role in the organization of the neural circuitry and in synapse maturation [64]. CDH18 is elevated in CSF of pregnant women [65]; even if the biological meaning of its variations is unknown, this finding suggests that CDH18 is a detectable metabolite that varies with the patient's condition.…”
Section: Cdh18mentioning
confidence: 99%